Case Report: Intestinal Nodular Lymphoid Hyperplasia as First Manifestation of Activated PI3Kδ Syndrome Due to a Novel PIK3CD Variant - Marzollo, Antonio; Bresolin, Silvia; Colavito, Davide; Cani, Alice; Gaio, Paola; Bosa, Luca; Mescoli, Claudia; Rossini, Linda; Barzaghi, Federica; Perilongo, Giorgio; Leon, Alberta; Biffi, Alessandra; et al. (Frontiers in Pediatrics, 2021)
Nodular lymphoid hyperplasia (NLH) is a lymphoproliferative disease caused by non-clonal expansion of lymphoid cells in the gut mucosa. Little is known about the pathogenesis of NLH, which is often disregarded as an insignificant or para-physiologic phenomenon. We present the case of a girl with isolated diffuse NLH (extending from the stomach to the rectum) caused by activated PI3Kδ syndrome (APDS) due to the novel p.Glu525Gly variant in PIK3CD. The gain-of-function effect of the variant was confirmed by demonstration of over activation of the Akt/mTOR pathway in the patient's cells. APDS diagnosis led to treatment with sirolimus, which resulted in the complete remission of NLH and in the prevention of extra intestinal complications. In conclusion, we identify APDS as a novel cause of isolated NLH and suggest that patients with severe pan-enteric NLH should be screened for this disorder that may not be apparent on first-line immunological testing.